Maternal vitamin D supplementation during pregnancy and lactation to prevent acute respiratory infections in infancy in Dhaka, Bangladesh (MDARI trial): protocol for a prospective cohort study nested within a randomized controlled trial. Issue 1 (December 2016) - Morris, Shaun; Pell, Lisa; Rahman, Mohammed; Dimitris, Michelle; Mahmud, Abdullah; Islam, M.; Ahmed, Tahmeed; Pullenayegum, Eleanor; Kashem, Tahmid; Shanta, Shaila; Gubbay, Jonathan; Papp, Eszter; et al.
Abstract Background Early infancy is a high-risk period for severe acute respiratory infection (ARI), particularly in low-income countries with resource-limited health systems. Lower respiratory tract infection (LRTI) is commonly preceded by upper respiratory infection (URTI), and often caused by respiratory syncytial virus (RSV), influenza and other common community-acquired viral pathogens. Vitamin D status is a candidate modifiable early-life determinant of the host antiviral immune response and thus may influence the risk of ARI-associated morbidity in high-risk populations. Methods/Design In the Maternal Vitamin D for Infant Growth (MDIG) study in Dhaka, Bangladesh (NCT01924013), 1300 pregnant women are randomized to one of five groups: placebo, 4200 IU/week, 16, 800 IU/week, or 28, 000 IU/week from 2nd trimester to delivery plus placebo from 0–6 months postpartum; or, 28, 000 IU/week prenatal and until 6-months postpartum. In the Maternal Vitamin D for ARI in Infancy (MDARI) sub-study nested within the MDIG trial, trained personnel conduct weekly postnatal home visits to inquire about ARI symptoms and conduct a standardized clinical assessment. Supplementary home visits between surveillance visits are conducted when caregivers make phone notifications of new infant symptoms. Mid-turbinate nasal swab samples are obtained from infants who meet standardized clinical ARI criteria. Specimens are tested by polymerase chain reaction (PCR) for 8 viruses (influenza A/B, parainfluenza 1/2/3, RSV, adenovirus, and human metapneumovirus), and nasal carriage density ofStreptococcus pneumoniae. The primary outcome is the incidence rate of microbiologically-positive viral ARI, using incidence rate ratios to estimate between-group differences. We hypothesize that among infants 0–6 months of age, the incidence of microbiologically-confirmed viral ARI will be significantly lower in infants whose mothers received high-dose prenatal/postpartum vitamin D supplements versus placebo. Secondary outcomes include incidence of ARI associated with specific pathogens (influenza A or B, RSV), clinical ARI, and density of pneumococcal carriage. Discussion If shown to reduce the risk of viral ARI in infancy, integration of maternal prenatal/postpartum vitamin D supplementation into antenatal care programs in South Asia may be a feasible primary preventive strategy to reduce the burden of ARI-associated morbidity and mortality in young infants. Trial registration NCT02388516, registered March 9, 2015.